Analisis Keberadaan Dan Pengembangan Gardu Induk Distribusi 20 kV Di Kota Pekanbaru - Sukma, Dian Yayan; M, Ferry; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Substation as a component of power system plays an important role in the continuity of the supply of electric to consumers that continues to increase each year. If the electrical load is borne by the substation is greater than the capacity of the substation, the substation will experience overload which resulted in the supply of electricity to consumers stalled. These condition must be anticipated as early as possible by PT. PLN (Persero) Pekanbaru CityArea as the provider of electric energy. In this thesis, the author conducted an analysis the existence and development of 20 KV distribution substation in City of Pekanbaru to evaluatethe existing condition which includes loading the transformer and a broad service area on the substation-substation in the city of Pekanbaru then be combined with forecast informationpeak load growth in every district, the density of the total load and peak load in Pekanbaru Resulsts in development of substation Garuda Sakti occured in 2015 with up rating andaddition of 1 unit transformer, in 2016 the development with addition 1 unit transformer, in 2019 the development with made planning construction of new substations. Results indevelopment of substation Teluk Lembu in 2020 with the addition 1 unit transformer and in 2023 made planning construction of new substation. With the construction of the newsubstation will take over most of substation loading on Garuda Sakti and Teluk Lembu.Keywords : Load growth forecast, Transformer, Develoment of substation